METHODS OF IMPLEMENTATION OF INFORMATION PROTECTION SYSTEM - Tojiboev Ibrokhimjon Tojalievich; Mamirkhojayev Muhammadamin Mavlonjonovich; Umaraliyev Jamshidbek Tokhtasinovich; Sotvoldiyeva Mohirakhon Bakhromjon qizi; Toychibaev Abbosjon Eraliyevich (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, legal methods of information protection and the main directions of security for electronic computing. In addition, it provides information about the type of confidential information and the principles of their operation.